Market orientation and marketing innovation activities in the Czech manufacturing sector - Marek Vokoun; Romana Píchová (International Journal of Financial Studies, 2020)
Market competition drives organizations to higher efficiency. This paper analyses the relationship between the prevailing organization's market orientation and marketing innovation activities. The sample of organizations consists of business enterprises from the manufacturing sector in the Czech economy. Data come from the Community Innovation Survey in 2014 and are analyzed using the innovation process econometric modeling. This innovation survey covers the period of a 3 year J-curve of real GDP growth. Czechia is one of the most open economies in the world and has one of the largest shares of exports and imports to GDP. This paper evaluates four types of marketing innovation activities (design, pricing, placing and promotion methods) at the enterprise level as a factor of marketing capability. The analyzed sample consists of observations about new-to-the-market innovators and enterprises that did not engage in new-to-the-market innovation activities in the last three years. The second group are considered to be lower-level innovators, i.e., adaptors to technological change. This paper explores the relationship between local, national, European and World market orientation in addition to an enterprise's marketing innovation activities. The results suggest that not all types of marketing innovations are dependent on market orientation, while some have indirect positive and negative effects. Feedback and the future effects of marketing innovation activities are present at the enterprise level. Results also suggest that the marketing innovations of innovators form the manufacturing sector while they are dependent upon the strategies of enterprises to enter new geographical markets and gain the motivation to unlock new (hidden) demand.
Keywords: O31; M31; L60; 330; business performance; exporters; innovation strategies; international competition; manufacturing; market orientation; marketing capabilities; marketing innovation; motivation